Impression of Scarcity Messages on Impulse Buying in E-commerce: Experimental Study: English - Ida Nur Aeni; Imas Nurani Islami; Ratieh Widhiastuti; Eva Nur Halimah (Cita konsultindo, 2025)
This research aims to determine whether there are differences in the influence of low and high levels of scarcity messages on impulsive buying mediated by perceived arousal and to examine the effect of the moderating role of financial literacy on the influence of perceived arousal on impulsive buying. The method used in this research is an experimental research method with a factorial research design of 2 (limited-quantity scarcity: high vs low) x 2 (limited-time scarcity: high vs low), the sample in this study was 82 participants. The research results show that there is no difference in perceived arousal when faced with a message of scarcity, however, perceived arousal can encourage consumers to make impulsive purchases and financial literacy is not able to moderate the relationship between perceived arousal and impulsive purchases. This research implies that consumers need to increase self-control so as not to be led by arousal emotions when making purchasing decisions.